(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The given article describes the features of the lexical and grammatical composition of Avar gender paremiological units characterizing women: substantive and verbal evaluative and symbolic lexical units that form positive and negative images of women are identified and interpreted; characterized by connotative components of gender-related paremiological images; the adversary-concessive semantic relations characteristic for the studied paremiological units were demonstrated; the attention is paid to the peculiarities of functioning of adjectival components in the described proverbs and sayings (participles, full and short forms of adjectives) in the predicative function; determined the role of the alogism principle, on the basis of which separate national-cultural images of women are built; characterized oppositionally (antonymously) opposed lexical units that form alogism relations; identified some unusual morphological forms with the value of a deprecated negation, used in the composition of expressive syntactic structures; the national-cultural components of some symbolic lexical components of the studied paroemiological units are determined. Key words: Avar language, paremias, female images, lexical and grammatical features, principle of alogism , connotations, semantic relations. DOI 10.18522/1995-0640-2020-1-53-61